Anti-TNF drug and antidrug antibody level monitoring in IBD: a practical guide. Issue 2 (21st January 2015) - Hendy, Philip; Hart, Ailsa; Irving, Peter
Abstract : The antitumour necrosis factor (TNF) medications, adalimumab and infliximab, play an important role in the management of both Crohn's disease and ulcerative colitis. For those in whom anti-TNF is effective, the therapy is associated with fewer symptoms, improved quality of life and disease and surgery-free survival. Unfortunately, up to 30% of patients will fail to respond to anti-TNF drugs while up to 50% of those who do see an initial response will lose response at some point. The introduction of drug monitoring for anti-TNFs, including drug level and antidrug antibody level testing allows a more personalised management of patients and improves patient outcomes. This article reviews the data for the use of anti-TNF monitoring and presents a 'how to' guide for clinicians.